Adaptive AI-Driven Formative Assessment in Early Childhood Education: A Systematic Review and Meta-Analysis on Cultivating Social-Emotional Learning and Early Moderation - Sari, Nurratri Kurnia; Wicaksana, Muhlis Fajar; Rahman, Md. Anisur (Universitas Nahdlatul Ulama Surabaya, 2025)
In today's era of digital transformation and the dominance of artificial intelligence, cognitive and social-emotional skills, such as social-emotional learning (SEL) and early moderation, have become vital competencies for students from an early stage of education. Adaptive instructional systems (Adaptive AI)-based instruction integrated with automated formative assessment is seen as an effective and creative strategy to enhance these skills through in-depth personalized learning. Over the past two decades, research on immersive technology has increased rapidly, but evaluation of its impact on character development and moderation attitudes in early childhood remains very limited. This study evaluates the impact of Adaptive AI-driven instruction on students' SEL skills and moderation behaviors, and systematically investigates the key factors contributing to their cognitive and affective development. The primary objective of this study is to map the effectiveness of AI-based formative assessment in monitoring the development of digital tolerance and resilience values ​​from an early age through integrative quantitative evidence. The method used was a Systematic Literature Review (SLR) and meta-analysis of 137 empirical studies indexed in the Scopus database from 2000 to 2026. Data analysis was conducted using the Google Colab platform using the R programming language (metafor package) to calculate effect sizes and ensure data transparency. Key findings indicate that adaptive instructional systems have a significant positive impact on children's emotional maturity and inclusive attitudes. Variables such as scaffolding features in AI interactions and multimodal communication strategies were shown to significantly influence outcomes, while geographic location factors had no significant impact. In conclusion, the ethical integration of AI has profound implications for the development of early childhood education curricula based on digital resilience and moderation.